The problem of indifference and homogeneity in Austrian economics: Nozick’s challenge revisited - Wysocki, Igor (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
The pivotal point in the Austrian literature on homogeneity, choice and indifference was constituted by Nozick’s On Austrian Methodology. Nozick provoked a long debate on the above notions within Austrianism. The aim of this paper is to elaborate such an account of homogeneity that would take the sting out of Nozick’s challenge and allow for non-trivial formulation of the law of diminishing marginal utility. Hence, we shall first take a closer look at the debate on indifference within the Austrian camp, while defending and building upon the Hoppean account vis-à-vis Block’s criticism. Our justification of the Hoppean position shall consist in showing that his account of the correct description of an action is not an ad hoc move aimed at solving just one problem of indifference but is highly intuitive and widely applicable. We conclude by restating the above-mentioned law, thus demonstrating that the Nozickian objection can be successfully replied.
Keywords: indifference; choice; homogeneity; Nozick's challenge